2018
DOI: 10.1038/s41592-018-0045-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide C-SWAT library for high-throughput yeast genome tagging

Abstract: Here we describe a C-SWAT library for high-throughput tagging of Saccharomyces cerevisiae open reading frames (ORFs). In 5,661 strains, we inserted an acceptor module after each ORF that can be efficiently replaced with tags or regulatory elements. We validated the library with targeted sequencing and tagged the proteome with bright fluorescent proteins to quantify the effect of heterologous transcription terminators on protein expression and to localize previously undetected proteins.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 29 publications
2
106
0
Order By: Relevance
“…In these all genes were modified in the same manner, i.e. by gene deletion or by tagging with a fluorescent protein or affinity tag (Gavin et al, 2002;Ghaemmaghami et al, 2003;Huh et al, 2003;Meurer et al, 2018;Winzeler et al, 1999). We believe that in mammalian cell culture similar endeavors are now at reach using the approach presented in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In these all genes were modified in the same manner, i.e. by gene deletion or by tagging with a fluorescent protein or affinity tag (Gavin et al, 2002;Ghaemmaghami et al, 2003;Huh et al, 2003;Meurer et al, 2018;Winzeler et al, 1999). We believe that in mammalian cell culture similar endeavors are now at reach using the approach presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, this constitutes a compromise, and includes the possibility that important gene regulatory sequences are omitted from the tagged gene. While for mammalian cells no global data set about the regulatory impact of the 3'-UTR on gene expression is available, data from yeast, where seamless tagging was compared with tagging using a generic 3'-UTR, demonstrated that only about 11% of the genes were impacted in their expression more than 2-fold (Meurer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations